Pengaruh Motivasi Kerja Dan Kompetensi Terhadap Kinerja Pegawai Di UPTD Puskesmas Adipala II Kabupaten Cilacap - Riswanto Riswanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Employee performance in general is a manifestation of the work done by employees which is usually used as a basis or reference for evaluating employees in an organization. Good or bad performance is determined by the good and bad of existing human resources. To achieve performance, causal factors are needed that encourage better performance such as work motivation and competence. So the purpose of this study was to find out and describe the influence of work motivation and competence on employee performance at the UPTD Adipala II Health Center, Cilacap Regency. The method used is descriptive with a quantitative approach. The results of the study show that motivation has a positive and significant effect on employee performance. This means that if motivation increases, it will be followed by an increase in employee performance. Competence has a positive and significant effect on employee performance. This means that if competence increases, it will be followed by an increase in employee performance. Motivation and competence have a positive and significant effect on employee performance. This means that if motivation and competence increase, it will be followed by an increase in employee performance